The assessment of catagenetic source rock zoning in the kyndal graben of the bureya basin using paleotectonic and paleotemperature modeling software (the far east of Russia); Проблемы геологии и освоения недр; Т. 2 - Prokhorova P. N. (Геология, горное и нефтегазовое дело (доклады на английском и немецком языках), 2018)
Заглавие с экрана